Challenges of using asthma admission rates as a measure of primary care quality in children: An international comparison. Issue 4 (October 2021) - Lut, Irina; Lewis, Kate; Wijlaars, Linda; Gilbert, Ruth; Fitzpatrick, Tiffany; Lu, Hong; Guttmann, Astrid; Goldfield, Sharon; Lei, Shaoke; Gunnlaugsson, Geir; Hrafn Jónsson, Stefán; Mechtler, Reli; et al.
Objectives: To demonstrate the challenges of interpreting cross-country comparisons of paediatric asthma hospital admission rates as an indicator of primary care quality. Methods: We used hospital administrative data from >10 million children aged 6–15 years, resident in Austria, England, Finland, Iceland, Ontario (Canada), Sweden or Victoria (Australia) between 2008 and 2015. Asthma hospital admission and emergency department (ED) attendance rates were compared between countries using Poisson regression models, adjusted for age and sex. Results: Hospital admission rates for asthma per 1000 child-years varied eight-fold across jurisdictions. Admission rates were 3.5 times higher when admissions with asthma recorded as any diagnosis were considered, compared with admissions with asthma as the primary diagnosis. Iceland had the lowest asthma admission rates; however, when ED attendance rates were considered, Sweden had the lowest rate of asthma hospital contacts. Conclusions: The large variations in childhood hospital admission rates for asthma based on the whole child population reflect differing definitions, admission thresholds and underlying disease prevalence rather than primary care quality. Asthma hospital admissions among children diagnosed with asthma is a more meaningful indicator for inter-country comparisons of primary care quality.